Building Regional Economic Stability Through Effective Legal Protection for Micro, Small, and Medium Enterprises in Indonesia - Nurhadi; Hardyansah, Rommy; Putra, Arif Rachman (Journal of Social Science Studies, 2023)
Legal protection of Micro, Small and Medium Enterprises (MSMEs) plays an important role in maintaining regional economic stability. MSMEs contribute to the national Gross Domestic Product and create more jobs in Indonesia. They often face challenges such as limited access to financing and legal uncertainty. Adequate legal support, including intellectual property rights protection and ease of licensing, can improve the competitiveness of MSMEs and help them survive in crisis situations, as seen during the COVID-19 pandemic. This research aims to explore the relationship between MSMEs legal protection and regional economic stability, as well as identify policies that can strengthen MSMEs resilience. The method used is normative juridical analysis with a qualitative approach, which involves literature study and analysis of legal documents. Results show that effective legal protection supports the sustainability of MSMEs, and contributes to local economic growth. It is important for the government to continue strengthening regulations that support MSMEs, create a conducive business environment, and ensure equitable distribution of assistance. MSMEs can grow and contribute more to the national economy.